Methanotroph community structure and processes in an inland river affected by natural gas macro-seeps. Issue 10 (9th September 2021) - Burrows, Ryan M; van de Kamp, Jodie; Bodrossy, Levente; Venarsky, Michael; Coates-Marnane, Jack; Rees, Gavin; Jumppanen, Paavo; Kennard, Mark J
ABSTRACT: Methane availability in freshwaters is usually associated with spatial-temporal variation in methanogenesis. Unusually, however, natural gas macro-seeps occur along the Condamine River in eastern Australia which elevate ambient water-column methane concentrations more than 3, 000 times. We quantified the spatial-temporal variation in methane oxidation rates and the total microbial and methanotroph community composition (through the amplification and sequencing of 16S rRNA and particulate methane monooxygenase ( pmoA ) genes), and the factors mediating this variation, in reaches with and without macro-seeps. Sediment methane oxidation rates were, on average, 29 times greater, and the abundance of methanotrophs significantly higher, in the vicinity of methane macro-seeps compared to non-seep sites. Methylocystis was the most abundant methanotroph group at all sites, but type Ib methanotrophs showed the steepest increase in abundance at seep sites. pmo A gene analysis identified these as clade 501, while 16S rRNA gene analysis identified these as the closely related genus Methylocaldum . Sediment methane oxidation rates and the relative abundance and composition of benthic microbial communities were primarily influenced by methane availability which was in turn related to variation in river discharge. Methane-derived carbon may be an important energy source for the aquatic food webs in reaches affected by natural gas macro-seeps. Abstract : Natural gas macro-seeps on the Condamine River elevates ambient methane concentrations more than 3000 times and substantially alters the microbial community structure and rates of methane oxidation.